The SIST-M: Development, reliability and cross-sectional validation of a brief structured Clinical Dementia Rating interview - Okereke, Olivia I. (2011)
BACKGROUND: The Clinical Dementia Rating (CDR) and CDR-Sum-of-Boxes (CDR-SB) can be utilized to grade mild but clinically important cognitive symptoms. However, sensitive clinical interview formats are lengthy. OBJECTIVE: To develop a brief instrument for obtaining CDR scores, and to assess its reliability and cross-sectional validity. METHODS: Using legacy data from expanded interviews conducted among 347 community-dwelling, older adults in a longitudinal study, we identified 60 questions about cognitive functioning in daily life–out of a possible 131– using clinical judgment, inter-item correlations, and principal components analysis. Items were selected in one cohort (n=147), and a computer algorithm for generating CDR scores was developed in this same cohort and re-run in a replication cohort (n=200) to evaluate how well the 60 items retained information from the original 131. Then, short interviews based on the 60 items were administered to 50 consecutively-recruited elders, with no or mild cognitive symptoms, at an Alzheimer Disease Research Center. CDR scores based on short interviews were compared with those from independent long interviews. RESULTS: In the replication cohort, agreement between short and long CDR interviews ranged from κ =0.65–0.79, with κ =0.76 for Memory; κ =0.77 for global CDR; ICC (intra-class correlation coefficient) for CDR-SB=0.89. In the cross-sectional validation, short interview scores were slightly lower than those from long interviews, but good agreement was observed: κ ≥ 0.70 for global CDR and Memory; ICC for CDR-SB=0.73. CONCLUSIONS: The SIST-M is a brief, reliable and sensitive instrument for obtaining CDR scores in persons with symptoms along the spectrum of mild cognitive change.